(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the incidence of patent ductus arteriosus in preterm infants and to evaluate the effectiveness of pharmacological closure of the ductus arteriosus in preterm neonates at the National Hospital of Obstetrics and Gynecology. Method: This retrospective and prospective descriptive study included 267 preterm infants born at < 32 weeks’ gestation admitted to the Neonatal Center, National Hospital of Obstetrics and Gynecology. All infants underwent routine echocardiography on days 3-4 after birth or earlier if patent ductus arteriosus was suspected. Infants were classified into three groups: closed ductus, patent ductus arteriosus without hemodynamic significance, and hemodynamically significant patent ductus arteriosus. Infants with hemodynamic significant patent ductus arteriosus received Ibuprofen or Paracetamol for medical closure. The study assessed the efficacy of both drugs, as well as changes in clinical and echocardiographic parameters before and after treatment, and evaluated complications associated with hemodynamic significant patent ductus arteriosus. Results: Patent ductus arteriosus was diagnosed in 61.4%, including 28.7% of hemodynamic significant patent ductus arteriosus, birth weight < 1000g (63.8%) and gestational age < 28 weeks (55.3%). Among those, 89.4% infants received pharmacological treatment, with successful ductal closure achieved in 69%. The success rates were 54.2% for Paracetamol and 64% for Ibuprofen. Clinical symptoms improved markedly after treatment. The mean ductal diameter decreased from 2.73 ± 0.65 mm before treatment to 1.09 ± 1.22 mm after treatment, and the LA/Ao ratio decreased from 1.87 ± 0.39 to 1.42 ± 0.33. Neonatal sepsis increases the risk of hemodynamic significant patent ductus arteriosus by approximately sixtimes. Infants with hemodynamic significant patent ductus arteriosus had higher rates of pulmonary hemorrhage, sepsis, intraventricular hemorrhage, and bronchopulmonary dysplasia compared with those without hemodynamic significant patent ductus arteriosus. Conclusions: Pharmacological treatment hemodynamic significant patent ductus arteriosus with Ibuprofen or Paracetamol is effective in achieving patent ductus arteriosus closure in preterm infants. Treatment reduces clinical symptoms as well as reduces ultrasound parameters. Hemodynamic significant patent ductus arteriosus is associated with an increased risk of severe complications, so routine echocardiography is required in preterm infants, especially extremely preterm infants.